Three-Dimensional Measurement of Maxillary Involvement in Hemifacial Microsomia in Children. Issue 2 (March 2020) - Xu, Xi; Zhang, Zhi-yong; Li, Bing-hang; Tang, Xiao-jun; Yin, Lin; Liu, Wei
Abstract : Abstract: In hemifacial microsomia (HFM), the aberrant mandible structure has always been the focus of attention. How the maxillary development being affected is not clear. The authors sought to comprehensively evaluate the hemifacial maxillary deficiency and to assess for Pruzansky-Kaban score correlation. This is a retrospective research of children with HFM. Demographic information were recorded, and computed tomographic scan were reconstructed and analyzed by segmentation, volumetric and cephalometric measurements. Analyses involved paired t -test, independent sample t -test and one-way analyses of variance. Demographic information revealed 67 patients diagnosed with HFM were included: 10.4 percent type I, 38.8 percent IIa, 28.4 percent type IIb, 22.4 percent type III. The maxillary total volume was found to be significantly decreased on the affected side in patients with type IIa ( P = 0.0426) and IIb ( P = 0.0004). No notable differences in maxillary sinus volume were found. No significant differences in maxillary width measurements were found between groups type I and III. A descending trend in maxillary bone volume ratio, an increasing trend in maxillary posterior width ratio and a decreasing trend in maxillary middle height ratio was observed from group I to IIb ( pmbv* = 0.020; pmpw* = 0.002; pmmh* = 0.004). This study comprehensively characterized the hemifacial microsomia maxillary deficiency. For maxillary total volume and transverse development, the type III group presented characteristics similar to the type I group. We concluded that the severity of maxillary deficiency is not completely consistent with the mandibular deformity classification. Abstract : Supplemental Digital Content is available in the text